Research on differentiation of influential factors of key account satisfaction in fixed communication industry - Botao XIA (Dianxin kexue)
Based on the existing findings of previous customer satisfaction studies and a telecom operator's key account satisfaction assessment results of 5 consecutive years,CNCCSI model was established to study influential factors of key accounts in fixed communication industry.Methods were discussed to segment key accounts in fixed communication industry through multiple indicator cluster analysis of influential factors of satisfaction and industry characteristic indicators.Clustering technology was used to divide 11 industries into 4 customer segments and demand character,concerned factors and satisfaction of each segment were analyzed.Aiming at a telecom operator's problems of present marketing service analysis of key accounts,improvement suggestions of market system were put forward.